ANALISIS PENGARUH BIAYA BAHAN BAKU DAN TENAGA KERJA TERHADAP EFISIENSI BIAYA PRODUKSI : STUDI KASUS PADA PABRIK TEMPE UWAIS DI KOTA MEDAN - Mei Dara Lestari saragih; Tresia pariama manalu; Dhea evangkye sinaga; Hamonangan Siallagan (STKIP Subang, 2026)
This study aims to analyze the effect of raw material costs and labor costs on production cost efficiency at the Uwais Tempe Factory in Medan City. This study uses a quantitative approach with multiple linear regression analysis using SPSS version 26. The research data were obtained from the Uwais Tempe Factory's production cost report for 24 months. The results show that raw material costs and labor costs partially have a positive and significant effect on production cost efficiency. In addition, both variables simultaneously also have a significant effect on production cost efficiency. The results show that good management of raw materials and labor can improve production efficiency, reduce cost waste, and increase company productivity. Thus, effective control of production costs is very important in maintaining business sustainability and competitiveness.